Language Choices in the Realm of New Media in A Multilingual Society in Denpasar City - Suastra, I Made (International Seminar on Austronesian Languages and Literature, 2021)
The choice of language in communication is greatly determined by the understanding of the message conveyed in a multilingual society. Sociolinguistically, The choice of language in different domains is determined by many factors, including age, gender, education, and other social categories. This study focuses on language use and language choice in the realm of new media in a multilingual society in the city of Denpasar. The objectives of this study are 1). to identify the types of new media domains used by Balinese as a means of communication, 2). to analyze the choice of language used by Balinese for communication using new media. This study utilizes some theories such as domain theory (Fishman, 1972), language choice (Holmes, 2013) and media ((McQuail, 2011; Vivian, 2008) as the basic framework of analysis. The research method applies a mixed sequential explanatory method that combines quantitative with qualitative methods (Creswell, 2009). The study was conducted in the city of Denpasar which is an area that reflects a multilingual speech community. The results of this study indicate that there are many new media used by Balinese speakers, including Facebook, WA, Instagram, TilTok, michat, etc., the favorites of the social media are Facebook, WA, and Instagram. There is a tendency for male speakers to use new media more than female, especially in Facebook, WA, Instagram. Regarding the choice of language, the speakers tend to mix between Balinese language and Indonesian became the dominant choice but a mixed language between Balinese, Indonesian and foreign languages ??are also used, while the Balinese language itself did not seem to be a choice in their communication on new media. This proved that the level of response of the speakers of Balinese to the new media is still low